In Vitro Formation of 3D-Spheroids by Human Endometrial Multipotent Mesenchymal Stromal Cells - Zlatska, Olena V.; Rodnichenko, Anzhela E.; Gubar, Olga S.; Zubov, Dmytro A.; Litvinova, Larisa S.; Todosenko, Natalia M.; Novikova, Svitlana N.; Vasyliev, Roman G. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 084–088